DIAGNOSIS AND PREVENTION OF CARIES DEVELOPMENT IN ORTHODONTIC TREATMENT (World Bulletin of Social Sciences, 2021)
The aim of study is to improve the diagnosis and prevention of the development of caries and its complications during orthodontic treatment.
Keywords: Orthodontic Treatment; Caries; Calcium Fluoride Crystals; development